Out-of-plane optical transmittance of 2D photonic macroporous silicon structures - Karachevtseva, L.A.; Glushko, A.E.; Ivanov, V.I.; Lytvynenko, O.O.; Onishchenko, V.F.; Parshin, K.A.; Stronska, O.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Optical transmission spectra of 2D photonic macroporous silicon structures are investigated. The absolute bandgap for high values of the out-of-plane component kz is situated between the second and third photonic bands. Essential reduction in the transmittance of electromagnetic radiation and the step formation are observed for wavelengths less than the optical period of structures due to directed and decay optical modes formed by macroporous silicon as a short waveguide. The absorption in the macroporous silicon structure is determined by a maximum of the longitudinal component of electromagnetic waves, its interaction with 2D surface oscillations, and the appearance of polaritonic resonances.